Seismic Loads : Time-Saving Methods Using the 2018 IBC and ASCE/SEI 7-16 - Fanella, David A. (McGraw-Hill Education, 2022)
This publication provides structural engineers, educators, students, and other design professionals a concise, visual guide to the determination of structural loads due to seismic loads.